2002
DOI: 10.4049/jimmunol.168.9.4420
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Suppresses Proximal TCR Signaling in Resting Human CD4+ T Cells by Inhibiting ZAP-70 Tyr319 Phosphorylation: A Potential Role for Tyrosine Phosphatases

Abstract: The balance between positive and negative signals plays a key role in determining T cell function. CTL-associated Ag-4 is a surface receptor that can inhibit T cell responses induced upon stimulation of the TCR and its CD28 coreceptor. Little is known regarding the signaling mechanisms elicited by CTLA-4. In this study we analyzed CTLA-4-mediated inhibition of TCR signaling in primary resting human CD4+ T cells displaying low, but detectable, CTLA-4 cell surface expression. CTLA-4 coligation with the TCR resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 43 publications
1
68
0
Order By: Relevance
“…This agrees with reports that SHP-1 does not dephosphorylate the TCR or BCR ITAMs (16,26,27). Yet, several reports have suggested that SHP-1 can dephosphorylate ITAMs.…”
Section: Discussionsupporting
confidence: 82%
“…This agrees with reports that SHP-1 does not dephosphorylate the TCR or BCR ITAMs (16,26,27). Yet, several reports have suggested that SHP-1 can dephosphorylate ITAMs.…”
Section: Discussionsupporting
confidence: 82%
“…The exact mechanisms by which CTLA-4 is able to inhibit T-cell activation have been studied extensively; cross-linking CTLA-4 in the context of CD3/CD28 stimulation has been shown to inhibit T-cell proliferation via interaction with proximal intracellular signalling molecules such as TCR-z [7,64,65]. We show here that CTLA-4 fails to regulate proximal T-cell signalling and T-cell proliferation in lupus patients.…”
Section: Discussionmentioning
confidence: 76%
“…The most well studied examples of such coreceptors are the CD28/CTLA-4 family members (3,4). Additional regulatory molecules that function as T cell coactivating or coinhibitory receptors have been described (2).…”
mentioning
confidence: 99%